Strategic Technological Integration And Quality Management Standards For Personnel Output: Integrasi Teknologi Strategis Dan Standar Manajemen Mutu Untuk Keluaran Personalia - Muhammad Iqbal Rusdi; Mas Oetarjo (Proceedings of The ICECRS, 2024)
General Background Technological innovation serves as a primary pillar for corporate transformation, automating routine tasks and providing accurate data for organizational decisions. Specific Background PT Mustika Tembakau Indonesia experiences operational inefficiencies and productivity declines because personnel often lack clear understanding of their daily responsibilities. Knowledge Gap The recent adoption of digital systems lacks supporting operational guidelines, causing input errors and systemic confusion among users. Aims This study explores targeted administrative strategies and technological adaptations to maximize personnel output within the tobacco manufacturing sector. Results Strategic interventions involve implementing ISO 9001:2015 frameworks by formulating comprehensive operating procedures, work instructions, and customized data collection forms. Furthermore, management conducted competency mapping and delayed training programs encompassing product knowledge, 5R workspace organization, and precise system module operations. Novelty This research integrates international certification frameworks directly with localized technological software adaptation to resolve specific role ambiguities. Implications Aligning technological software with structured competency training and clear administrative guidelines ensures long-term operational efficiency and sustainable business growth. Highlights: Formulating detailed operating procedures clarifies daily responsibilities and resolves operational confusion. Software implementation requires aligned administrative guidelines to prevent data input errors. Competency mapping and targeted training align worker skills with international certification criteria. Keywords: Enterprise Resource Planning, Standard Operating Procedures, Human Resource Management, Quality Management Standards, Personnel Competency Mapping